Effects of gender-based violence on students" well-being: A case of Mufulira College - Samakao, Misheck (HTS teologiese studies, 2023)
Institutions of higher learning have continued to record high cases of gender-based violence (GBV) despite all efforts put in place to fight the vice. The most common forms of GBV are physical, sexual assault and psychological violence. Women and girls make up the majority of the GBV victims worldwide. For many years, institutions of higher learning have proved to be fertile environments for GBV cases.The purpose of this study was to investigate effects of GBV on the well-being of students in institutions of higher learning in Zambia.The study employed a mixed research methodology, and it was anchored on pragmatic philosophical paradigm. An explorative study design was used. Data were collected using both probabilistic and non-probabilistic methods, and the sample size was 150 respondents. The main findings of the study showed both academic and non-academic effects of GBV on students and included stigma, low academic performance, mental and psychological trauma as well as high drop outs.Contribution: The study highlighted effects of GBV as being both academic and non-academic in nature. Once students and staff ignore the word of God spoken in scriptures and begin to follow their egos, the consequences are devastating. For scriptures says love one another, forgive each other and bear each other’s burdens in love. Do unto others as you would want then to do unto you. For where there is love, no one will desire to hurt others. Where there is no love of God or forgiveness, there is pain and damage that can spoil someone’s future, especially that of the youth.